2018
DOI: 10.1080/17435390.2018.1482378
|View full text |Cite
|
Sign up to set email alerts
|

Cationic polystyrene nanoparticle and the sea urchin immune system: biocorona formation, cell toxicity, and multixenobiotic resistance phenotype

Abstract: In order to assess the impact of nanoplastics on marine species, polystyrene nanoparticles (PS NPs) have been largely used as model particles. Here we studied the effects of 50 nm amino-modified PS-NH on Mediterranean sea urchin Paracentrotus lividus immune system cells (coelomocytes) in the presence of celomic fluid (CF) and at different NP concentrations (1, 5, 10, and 25 μg mL) and experimental conditions (absence or presence of EDTA). PS-NH acquired a protein corona once incubated with CF, dominated by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 120 publications
5
44
0
Order By: Relevance
“…Ecotoxicological effects of MPs/NPs on marine phyto/zooplanktons, invertebrates, and plants are widely documented [20][21][22][23][24][25][26][27][28][29][30], and have been recently reviewed [5,[31][32][33]. MPs/NPs could also be ingested and accumulated in larger marine fauna by trophic transfer from prey to predator, as demonstrated earlier with invertebrates, such as mussel-consuming crabs [34].…”
Section: Introductionmentioning
confidence: 88%
“…Ecotoxicological effects of MPs/NPs on marine phyto/zooplanktons, invertebrates, and plants are widely documented [20][21][22][23][24][25][26][27][28][29][30], and have been recently reviewed [5,[31][32][33]. MPs/NPs could also be ingested and accumulated in larger marine fauna by trophic transfer from prey to predator, as demonstrated earlier with invertebrates, such as mussel-consuming crabs [34].…”
Section: Introductionmentioning
confidence: 88%
“…Amino-modified polystyrene particles acquired a protein corona once incubated with celomic fluid, dominated by the toposome precursor protein, which triggers particle−coelomocytes interactions and toxicity. 87 Wegner et al showed that 30 nm polystyrene nanoparticles, that were tested at concentrations of 0.1−0.3 g/L, have an adverse effect on the feeding behavior of the blue mussel Mytilus edulis because of a reduced filtering activity in the presence of the particles. 88 Pitt et al investigated the potential toxicity of polystyrene nanoparticles in developing zebrafish (Danio rerio) and characterized the uptake and distribution of the particles within embryos and larvae.…”
Section: Sources and Fate Of Plastic In The Environmentmentioning
confidence: 99%
“…[160] In the celomic fluid of sea urchins, the twosome precursor protein has been identified as a dominant component in protein corona formed on NH 2 −PS NPs, triggering the interaction between the NH 2 −PS NPs and the sea urchin immune system cells (i.e., coelomocytes). [209] Likewise, protein corona on TiO 2 NPs formed in the celomic fluid of sea urchins have been found to contain many proteins involved in cellular adhesion, cytoskeletal organization, and immune response. [210]…”
Section: Immunotoxicitymentioning
confidence: 99%